2014
DOI: 10.1021/ie501798f
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Reuse of Effluents from Palm Oil, Pulp, and Paper Mills as a Combined Substrate by Using Purple Nonsulfur Bacteria

Abstract: The growth of Rhodobacter sphaeroides NCIMB8253 was investigated under photoanaerobic conditions with different concentrations of palm oil mill effluent in a dual effluent growth medium. The influence of pulp and paper mill effluent as an alternative diluting agent on the bacterial growth was also investigated. During this study, it was determined that the use of pulp and paper mill effluent as a diluting agent promoted bacterial growth compared with the use of raw palm oil mill effluent medium alone. The cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“…CQK 01 to produce hydrogen Electronic Journal of Biotechnology 18 (2015) 221-230 [17]. PNSB are widely distributed in aquatic and wastewater environments [18,19,20]. They can be isolated from the environment using conventional enrichment techniques.…”
Section: Introductionmentioning
confidence: 99%
“…CQK 01 to produce hydrogen Electronic Journal of Biotechnology 18 (2015) 221-230 [17]. PNSB are widely distributed in aquatic and wastewater environments [18,19,20]. They can be isolated from the environment using conventional enrichment techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an introduction of PPME as a diluting agent in this study was necessary to promote photo-biohydrogen production by increasing the visibility of substrate and improving the light penetration into the system. Budiman et al 19 also reported that a combination of POME and PPME as single substrate could be applied as a suitable growth medium for R. sphaeroides because of the enhanced light penetration and faster adaptation in the diluted media. 19 Furthermore, the introduction of PPME (a low nitrogen source) helped increase the C/N ratio of photofermentation substrate (Table 1).…”
Section: Effect Of Pome Concentration On Biohydrogen Productionmentioning
confidence: 99%
“…Budiman et al 19 also reported that a combination of POME and PPME as single substrate could be applied as a suitable growth medium for R. sphaeroides because of the enhanced light penetration and faster adaptation in the diluted media. 19 Furthermore, the introduction of PPME (a low nitrogen source) helped increase the C/N ratio of photofermentation substrate (Table 1). It was reported that high C/N ratio promoted the production of biohydrogen by allowing PNS bacteria to dispose their excess energy and reducing power through production of hydrogen.…”
Section: Effect Of Pome Concentration On Biohydrogen Productionmentioning
confidence: 99%
See 2 more Smart Citations